(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
Digital repository of Croatian Academy of Sciences and Arts is a constantly developing platform. Currently, three new modules are being created to further upgrade customer service. One of them is DOI module, which will be able to assign Digital Object Identifier (DOI) number to any data type preserved in the repository. Another two new modules are closely connected. The first of them concerns the definition of documents and data publishing, while the other one relates to defining rules of data download directly from the repository. These two modules will enable electronic publication exchange, which will be unique in Croatia. DOI is assigned by publishers to articles or book chapters to provide a permanent link, assuring that the document can be discovered, even if the URL for the journal article changes. Therefore, the DOI guarantees scholars that readers will always be able to find their work, although the content on the internet is prone to being moved, restructured, or deleted. Assigning DOI is also a way to increase the visibility and citation in international databases and to provide one additional point when applying for financial support from the Croatian Ministry of Science, Education and Sports. DOI will be assigned to all the Academy’s journals. The procedure will be automatic, concerning the Academy’s large publication production. The Croatian Academy of Sciences and Arts has a long tradition of publication exchange with other world’s academies. The Academy’s library has collaborated with about 450 libraries around the globe for over 130 years. The tradition was established with the Academy’s first Rules of Procedure from 1867. Nowadays, publication exchange has severely dropped, due to financial situation. Postage costs have become problematic, and the exchange, which was one of the main sources of book supply, has become marginal. The list of partners in 2015 was shorter by half compared to the previous year. In 2015, 650 publications were sent to 100 locations in Croatia and to about 20 different addresses worldwide. Due to high shipping rates and lack of space in library buildings and similar institutions, as well as increased use of e-publications, the Management Board of the Croatian Academy of Sciences and Arts has approved the development of the new module which will enable electronic exchange of the Academy’s publications. The Publishing module should resolve the problems of publishing each of the Academy’s publications separately, including serials and monographs. The suggested delay period is 6 to 12 months after the final print publication date. In the meantime, these publications would only be available to institutions which are the Academy’s exchange partners. The Download module will allow users to download documents directly from the repository. These new modules should give a new life to this valuable but neglected tradition, which has enhanced library collections by providing publications which bypass the book trade network, including unique monographs of research institutes, proceedings of scientific conferences and symposiums, scholarly papers, and other publications on the latest research results.